An Epidemiologic Analysis of Diabetes in Colombia - Hernando Vargas-Uricoechea; Luz Ángela Casas-Figueroa (Ubiquity Press, 2016)
Background The burden of diabetes is a global problem, wherein the significant growth of diabetes in Colombia reflects a complex pathophysiology and epidemiology found in many other South American nations. Objectives The aim of this study was to analyze epidemiologic data from Colombia and the South American region in general to identify certain disease drivers and target them for intervention to curb the increasing prevalence of diabetes. Methods A detailed search was conducted using MEDLINE, SciELO, HINARI, LILACS, IMBIOMED, and Latindex databases, in addition to clinical practice guidelines, books, manuals, and other files containing relevant and verified information on diabetes in Colombia. Findings According to the International Diabetes Federation and the World Health Organization, the prevalence of diabetes in Colombia is 7.1% and 8.5%, respectively. In contrast, a national survey in Colombia shows a prevalence ranging from 1.84% to 11.2%, depending on how the diagnosis is made, the criteria used, and the age range studied. The prevalence exclusively in rural areas ranges from 1.4% to 7.9% and in urban areas from 1% to 46%. The estimated mean overall (direct and indirect) cost attributed to type 2 diabetes is 5.7 billion Colombian pesos (US $2.7 million). Diabetes is the fifth leading cause of death in Colombia with a rate of 15 deaths per 100,000 individuals. Conclusions Based on a clustering of factors, 4 relevant disease drivers emerge that may account for the epidemiology of diabetes in Colombia: demographic transition, nutritional transition, forced displacement/internal migration and urban development, and promotion of physical activity.